THE EFFECT OF CAREER DEVELOPMENT, WORK MOTIVATION, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Januari Wau; Purwanto (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This research aims to determine the effect of career development, work motivation, and job satisfaction on employee performance. In principle, human resources are one of the important factors in companies to achieve their goals. In this case, the researcher focuses on the job satisfaction variable as a mediating variable, including linking career development and work motivation to employee performance. Good career development, good motivation, and good job satisfaction can improve the results of employee performance in achieving company progress. In this research, the population was employees at MNC Studios company. The sample consisted of 265 people using a saturated sample. Data analysis used validity test, reliability test, Kaiser-Msyer-Olkin measures of sampling (KMO), and Measures of Sampling Adequacy (MSA). Data were analyzed using the Structural Equation Model (SEM) using Lisrel. Based on the result of testing the differences of coefficients on the research model, it showed that career development had a positive effect on employee performance and job satisfaction, job satisfaction had a positive effect on employee performance, and work motivation had a positive effect on job satisfaction and employee performance. Keywords: career development, work motivation, job satisfaction, employee performance